O-005 Endovascular therapy for acute ischemic stroke due to proximal intracranial anterior circulation occlusion treated beyond 8 h from time last seen well: a subset analysis of the merci registry. (12th July 2011) - Nogueira, R; Rymer, M; Smith, W; Lutsep, H; Walker, G; Liebeskind, D; Budzik, R; Devlin, T; Jovin, T
Abstract : Background and Purpose: Current selection criteria for reperfusion therapy are based on strict time windows. Recent data suggest that the mismatch between stroke severity and the amount of ischemic core at presentation may be more important than time when selecting patients for reperfusion treatment. We describe a prospectively collected cohort of anterior circulation stroke patients treated beyond 8 h from time last seen well (TLSW). Methods: The Merci Registry was a multicenter prospective registry of stroke patients with acute proximal intracranial arterial occlusion treated with Merci thrombectomy with or without adjunctive use of other devices or drugs. We performed a subset analysis of all consecutive patients meeting the following criteria: (1) anterior circulation occlusion, (2) treatment initiated >8 h from TLSW. Results: A total of 1000 patients were enrolled. Out of these, 112 were treated >8 h from TLSW and had complete follow-up data. Their baseline characteristics were as following: mean age, 62.7±15.1; male gender, 56.3%; baseline NIHSS 15.05±5.8 (median 15); mean time from symptom onset to puncture (hr), 13.82±10.6 (median, 10.74); mean procedural duration (hr), 2.06±1.0 (median 1.95); IV rt-PA use, 10.7%; IA thrombolytic use, 42%; GpIIbIIIa inhibitor use, 14.3%; other devices use, 46.5%; proximal occlusion stenting, 28.6%.The occlusion sites included: ICA, 41.1%; MCA-M1, 51.8%; MCA-M2, 7.1%. 50% of the patients had "wake-up" strokes while 18.8% of the patients had witnessed strokes with onset beyond 8 h from treatment. Successful revascularization (TICI≥2) was achieved in 81.3% (91/112) of the patients. Symptomatic intracranial hemorrhage (SICH) has been adjudicated according to the ECASS III criteria in 77/112 patients. There were 7/77 (9.1%) definite SICH and 4/77 uncertain SICH (5.2%) resulting a SICH rate not worse than 14.3%. The rate of good outcomes (90-day mRS≤2) was higher (37.8% vs 30.2%, p=0.12) and the 90-day mortality was significantly lower (18.8% vs 35.8%, p=0.0003) in the patients treated >8 h from TLSW as compared to the patients treated within 8 h. This was likely due to imbalances in age (67.5 vs 62.7) and baseline NIHSS (17.8 vs 15.05) as well as to a presumably higher rate of advanced (MRI or CT perfusion) imaging selection in the late treatment group. A subgroup of patients treated >8 h (n=50) was matched with PROACT-II patients for age (mean, 63 vs 64), baseline NIHSS (median, 17.5 vs 17), and site of occlusion (MCA-M1 and M2). These patients had similar rates of 90-day good outcome (36% vs 40%, p=NS) and mortality (16% vs 25%, p=NS) to the PROACT-II patients treated with intra-arterial therapy. Conclusions: In properly selected patients, endovascular therapy appears to be safe and beneficial even when treatment is initiated beyond 8 h from TLSW. The benefit of this approach compared to standard medical therapy should be assessed in a prospective randomized trial.